Westward propagation of substorm by THEMIS and ground-based observations. (15th September 2020) - Despirak, I.V.; Kozelova, T.V.; Kozelov, B.V.; Lubchich, A.A.
Abstract: The spatio-temporal dynamic of the substorm on December 24, 2014 in the interval from 16:00 to 17:00 UT was analyzed by data of large observational complex: magnetometers data by the Scandinavian network and by the longitudinal chain of the Russian auroral stations, the auroral dynamics in Apatity and data of THEMIS satellites. During the interval under study the THEMIS-E and THEMIS-D satellites were located in the midnight sector of the magnetosphere at r 8.5–10.3 RE and then passed over Siberia toward to Kola Peninsula. We show that the first substorm disturbances in the magnetosphere were in the region between the THE and THD satellites, and, according ground-based observations, it was projected to near Amderma station. Despite a sparse observational network in Siberia, the substorm intensification was possible to trace from the point of the origin at the longitude 80°E to the Scandinavia region at the longitude 30°E. Our estimates of the propagation velocities of the westward traveling surge (WTS) and so-called "auroral horn" (the arc ahead WTS) confirmed the values, obtained in the previous works. The occurrence of several structures of substorm in aurora (first small, localized auroral arc; beads structure in the auroras and the auroral horn) manifestates the propagation of the disturbances from the onset region to the West. It is shown also, that the fronts of dipolarization (DFs) and injection of energetic electrons in the magnetosphere were accompanied by activations of auroras: the brightening of arcs, the breakup and the appearance of WTS over Apatity. Highlights: Simultaneously observations by the THEMIS, by the aurora and magnetic disturbances. Analysis of the propagation of the disturbances from the onset region to the West. Several precursors of substorm in aurora were registered. Dipolarization fronts and injection of energetic electrons in the magnetosphere. Simultaneously observations of sudden intensification in aurora.